Penerapan Sistem Pakar untuk Diagnosis Kerusakan Smartphone Menggunakan Metode Forward Chaining Berbasis Android - Muhammad Syahuda Hasibuan; Abdul Halim Hasugian (TIN: Terapan Informatika Nusantara, 2026)
This study aims to design and develop an Android-based expert system application used to diagnose smartphone malfunctions using the Forward Chaining method. The main issue in this study is the limited knowledge of lay users in understanding the symptoms and types of smartphone malfunctions before seeking repairs. Research data was obtained through interviews with expert smartphone technicians at CarlCare Mobile Phone Repair Service in Medan, which is an official service center for Transsion vendors, namely Infinix, Itel, and Tecno. The data collected consists of 45 symptoms, 37 types of damage, 44 diagnostic rules, and 37 brief repair solutions. This application was developed using Flutter and Dart, with Firebase as the primary database and SQLite as the local database to ensure the application remains usable offline after synchronization is complete. The Forward Chaining method was applied by matching symptoms selected by the user with IF-THEN rules in the knowledge base to generate a diagnostic conclusion. The implementation results show that the app can display fault categories, symptom lists, diagnostic results, brief solutions, diagnostic history, as well as database synchronization and reset features. Black-box testing results indicate that all features function as expected. Thus, this app can help users obtain an initial diagnosis of Transsion smartphone faults in a simple, fast, and targeted manner.